Successful treatment with oral steroid and hydroxychloroquine in a patient with systemic lupus erythematosus upon COVID‐19 infection: A case report with detailed laboratory data. Issue 8 (24th August 2021) - Kondo, Makoto; Matsushima, Yoshiaki; Iida, Shohei; Umaoka, Ai; Nakanishi, Takehisa; Habe, Koji; Yamanaka, Keiichi
Abstract: The administration of glucocorticoid and hydroxychloroquine (HCQ) may be able to control systemic lupus erythematosus (SLE) activities under COVID‐19 infection by suppress the cytokine storm. Abstract : The administration of glucocorticoid and hydroxychloroquine (HCQ) may be able to control systemic lupus erythematosus (SLE) activities under COVID‐19 infection by suppress the cytokine storm.